Omnichannel retailing in the UK: a qualitative analysis and comparison with the Chinese market - Lin, Jun (2020)
This research aims to construct a framework to describe and analyse the business logistics models of omnichannel retailers in different sectors in the United Kingdom and China with a structural approach.